Analisis Kelengkapan Berkas Pada Kasus Pending / Gagal Klaim Guna Menunjang Ketepatan Klaim BPJS Di Rumah Sakit Umum Amira Purwakarta - Octaviani, Julia; Susanti, Ai Susi (CV. ITTC INDONESIA, 2024)
This study aims to determine the analysis of completeness of files in cases of pending/failed claims to support the accuracy of BPJS claims at the Amira General Hospital, Purwakarta.The research method used is a qualitative method with a systems approach through in-depth interviews as the primary data source and observations as secondary data in the form of inpatient claim files. From the results of the study it can be concluded that the results of the analysis of file completeness on the delayed/failed claim case variable is 91.8%, which means strong and 8.2% is influenced by other variables, namely error. 1. caused by doctors being busy in service 2. awareness of nurses to remind doctors to fill out medical resumes 3. expertise of claims officers and administration. The suggestions given to fix this problem are 1. Providing in-depth education to doctors regarding the importance of filling out a patient's medical resume is a responsibility that must be carried out in the midst of busy service, To reduce the impact of incomplete filling out of a Medical Resume, the competent authority shall issue a warning or sanction to doctors who do not comply. 2. Provide education to nurses to always remind doctors to fill out resumes when the doctor states that the patient is allowed to go home, 3. Hold meetings to discuss problems regarding claims file problems and hold training for claims officers and administration to develop skills on how to overcome problems that occur.